Parent–Child Associations in Accelerometer-Measured Physical Activity and Sedentary Behaviour: The FAMIPASS Study - Dagmar Sigmundová; Jaroslava Voráčová; Jan Dygrýn; Michal Vorlíček; Erik Sigmund (Children, 2024)
Parent–child patterns in objectively measured movement behaviours were the highlight of this study. A total of 381 families (337 mothers, 256 fathers, 190 daughters, and 191 sons) from 36 randomly selected schools and kindergartens provided valid accelerometer data. Sedentary behaviour and physical activity (PA) were assessed using ActiGraph accelerometers. Spearman’s rho was used to evaluate parent–child associations, while logistic regression analysis (the backward LR method) was used to recognize factors related to children’s achievement of PA recommendations. Results indicated that girls engaged more in light PA, while boys showed higher levels of moderate and vigorous PA. Mothers spent less time sitting and more time in light PA compared to fathers, resulting in higher total PA levels. Father–son pairs showed a stronger association in total PA than mother–son pairs. Children aged 6–10 years and those with mothers who engaged in more vigorous PA were more likely to meet PA recommendations compared to younger children and those with less active mothers.